DEVELOPMENT OF MAINTENANCE PERFORMANCE MEASUREMENT FRAMEWORK FOR PETROCHEMICAL INDUSTRY - RAZA, TAHIR (2017)
In order to extend equipment’s life and to reduce the frequent failures an appropriate maintenance strategy and effective maintenance performance measurement (MPM) system are required. This MPM system will highlight the reasons for under-performance in the planning and execution of maintenance activities. Generally, four parameters have been identified for MPM , i.e. reliability, availability, maintainability and safety (RAMS) parameters. However, mentioned parameters have not been used in the same framework, which has not comprehensively covered all aspects of MPM. Therefore, the main objective of this study is to propose a comprehensive MPM framework and performance indicators for petrochemical industry that cover all aspects of RAMS. The main motive for proposing MPM framework is to measure the value created by maintenance process. For this purpose initially, a detailed literature review has been conducted to identify different MPM systems. Moreover, the current MPM system of a local petrochemical industry has been acquired to observe and identify its lacking. Additionally, to support the primary objective an automated calculation mathematical model is also developed to ease the implementation. The developed model will identify the critical equipment using always better control (ABC) analysis technique due to the huge number of equipment in the industry, which assists in measuring the performance of critical equipment using proposed KPIs at three levels of management. In addition, to observe the failure behavior and predict the failures non- homogeneous Poisson process (NHPP) is also used. The proposed framework assists managers to detect and improve the under-performance maintenance activities in various processes at different levels utilizing RAMS parameters. To validate the applicability of the framework and mathematical model, reviews are obtained from experts to assess the validity and applicability of the framework as well as of mathematical model. The results from experts review show that this framework and mathematical model can be part of the maintenance performance improvement process.